MiRNAs as biomarkers of nutritional therapy to achieve T2DM remission in patients with coronary heart disease: from the CORDIOPREV study - Juan Francisco Alcala-Diaz; Antonio Camargo; Cristina Vals-Delgado; Ana Leon-Acuña; Helena Garcia-Fernandez; Antonio P. Arenas-de Larriva; Magdalena Perez-Cardelo; Marina Mora-Ortiz; Pablo Perez-Martinez; Javier Delgado-Lista; Maria Del Mar Malagon; Jose M. Ordovas; et al. (Nutrition & Diabetes, 2025)
Abstract Background Type 2 diabetes mellitus (T2DM) is currently a major global public health problem. Although disease remission is possible, few biomarkers have been identified which can help us select the diet that best promotes remission. Our aim was to study the potential of miRNAs as a tool to apply the Mediterranean diet or the low-fat diet in order to achieve T2DM remission in patients with coronary heart disease. Methods From the CORDIOPREV study (n = 1002), a prospective, randomized, single-blind, controlled dietary intervention trial, all patients newly diagnosed with T2DM (n = 190) at baseline were included in the present study. Of these, after adhering to a low fat or Mediterranean diet for 60 months, 73 patients showed T2DM remission (Responders) and 110 continued with the disease (Non-responders). Plasma levels of 56 miRNAs were determined by RT-PCR. Generalized linear model, ROC curves and COX regression analyses were performed. Results We observed that patients with low baseline plasma levels of miR-let7b-3p showed a high probability of T2DM remission after the consumption of a low-fat diet. In addition, patients with high levels of miR-141-5p, miR-182, and miR-192 at baseline showed a high probability of T2DM remission after following the Mediterranean diet. Scores built using miRNAs and clinical variables showed that high levels of a low-fat diet score and a high Mediterranean diet score were associated with a high probability of T2DM remission. Conclusion MiRNAs could be used as a tool for selecting the most efficient nutritional therapy (mediterranean or low-fat diet) to achieve T2DM remission in patients with coronary heart disease.